MINAT MENGGUNAKAN MOBILE BANKING MELALUI MANFAAT, KEMUDAHAN, FITUR LAYANAN DAN KEAMANAN - Latief, Fitriani; Dirwan, Dirwan; Ahmad Firman (Universitas Sulawesi Barat, 2024)
The purpose of this study is to examine the effect of benefits, convenience, service features and security on interest in using Mobile Banking. The approach used by researchers in this study is a quantitative approach. Researchers used primary data derived from original sources, obtained directly by researchers by distributing questionnaires directly to active students in Makassar City who use e-BCA mobile banking services. The population in this study is unknown, so the sample is calculated using the Lameshow formula, then this study uses accidental sampling techniques to take samples. The results found that the benefits, convenience, service features and security have a positive and significant influence on the interest in using Mobile Banking.